The Relationship and Influence Between 4p’s Subsidy and Financial Literacy Through Universal Basic Income Among the Beneficiaries of Selected Barangays in Iligan City - Eleoran, Angelica T.; Castillon, Marchie C.; Manlosa, Razel Mae D.; Bahala, Dianne Therese Marie C.; Abiol, Michael Jere’ D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The research aimed to explore the potential of Conditional Cash Transfer (CCT) systems in delivering financial education and influencing knowledge and behavior among beneficiaries residing in selected barangays within Iligan City. Cash transfer initiatives have gained significant traction in regions worldwide characterized by deep-seated poverty and inequality coupled with relatively unstable social protection systems. They are often hailed as a viable tool for bolstering social protection, endorsed by international organizations and aid agencies. Conditional cash transfers (CCTs) are being considered as a strategic approach to alleviating poverty while simultaneously making investments in human capital. Evaluations of CCT programs have demonstrated their potential in promoting greater utilization of healthcare and educational services. This study delves into the extent to which CCTs can enhance financial capability. One notable example is the Pantawid Pamilyang Pilipino (4Ps) program in the Philippines, a cash distribution initiative that channels resources into health and education with the aim of mitigating extreme poverty.